Pengaruh Ketrampilan Wirausaha, Inovasi Produk, Dan Kreativitas Terhadap Perkembangan Usaha Sportwear & Clothing - Ratna Wijayanti; Wahab Wahab; M. Fandi Maulana (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2022)
Purpose- This study aims to prove the effect of entrepreneurial skills, product innovation and creativity on business ventures at Philosophy Industries. Methodology-This research was conducted on customers of Philosophy Industries. The sample in this study were 97 respondents who were customers of Philosophy Industries. Data was collected by means of a questionnaire that was distributed online to Philosophy Industries customers. Findings-The results showed that the entrepreneurial skill variable had a positive effect on business ventures at Philosophy Industries as evidenced by the t-count value of 3.194 > t table 1.66123 with a significance of 0.002 <0.05. Product innovation has a positive effect on business ventures at Philosophy Industries as evidenced by the t arithmetic value of 5.229 > t table 1.66123 with a significance of 0.000 <0.05. Creativity has a positive effect on business ventures at Philosophy Industries as evidenced by t count 7.955 > t table 1.66123 with a significance of 0.000 <0.05.The purpose of this study is to prove whether there is an influence of ethnocentrism, brand image, lifestyle and product knowledge on batik purchasing decisions in Banyurip village. The sample of this research is 100 respondents, which are 100 batik consumers in Banyurip village. Data were collected by using a questionnaire that had been tested for validity and reliability. The results of this study were analyzed using multiple linear regression analysis